"Hello World". Issue 179 (1st September 2016) - Drori, Amit
Israeli artist and theatre maker Amit Drori reflects on the creative process that led him to create robotic-based performances. This was not an organized plan but rather an artistic evolution that began during his studies at the School of Visual Theatre in Jerusalem, and developed in his work as a professional artist. Coming from a background of visual theatre and puppetry, Drori's approach to robotics uses the knowledge and philosophy of puppetry and animation forms. Drori creates unique machines that are designed for emotional and poetic functionalities. "Hello world" follows the personal process of his artistic development, but also tries to discern the cultural roots and transformations of the accessibility of knowledge in the open source revolution.